Alginate drug delivery systems: application in context of pharmaceutical and biomedical research. (December 2014) - Jain, Dharmendra; Bar-Shalom, Daniel
Abstract Alginates are natural polymers widely used in the food industry because of their biocompatible, biodegradable character, nontoxicity and easy availability. The bioadhesive character of alginates makes them useful in the pharmaceutical industry as well. The application areas of sodium alginate-based drug delivery systems are many and these systems can be formulated as gels, matrices, membranes, nanospheres, microspheres, etc. Worldwide researchers are exploring possible applications of alginates as coating material, preparation of controlled-release drug delivery systems such as microspheres, beads, pellets, gels, fibers, membranes, etc. In the present review, such applications of alginates are discussed.